Rethinking Food Markets Initiative: Innovative approaches and key findings in the design and formulation of processed maize and bean-based products in Honduras - Peña, Meliza (International Maize and Wheat Improvement Center, 2024)
As part of the "Rethinking Food Markets" initiative, CIMMYT, in collaboration with national partners such as the Autonomous University of Honduras (UNAH), MATURAVE, and local SMEs involved in maize and bean processing, conducted a range of research activities focused on food processing from 2022 to 2024. Scope of a pilot Study: An analysis was conducted on SMEs processing maize and bean products. A total of 30 SMEs were interviewed in the Francisco Morazán, Cortés, Yoro, Comayagua, and El Paraíso departments. The goal was to identify key innovations in five critical areas: raw material sourcing, product design, production processes, marketing, and inter-business relationships. The study also highlighted the main barriers and limitations that hinder innovation. Additionally, innovations with potential for testing were identified, including 1) the design and formulation of maize chips with alternative flours, including bean flour; and 2) the packaging of whole cooked beans in vertical bags.